Sheep production systems of Beira Baixa - Almeida, J.P.F. (2011)
The region of Castelo Branco is the 4th main region of Portugal in number of ewes. Sheep production is the major importante activity of its farming systems. Beira Baixa Merino is the most common breed of the region and it is used as a triple purpose: milk, meat and wool. Nowadays, milk has becoming the most importante production. The new production conditions, with acession to the Common Market, lead the farmes to change some components of farming systems. To study how this changes must occur, an inquiry was made to the farmers, that allow a characterization of production systems, as the basis of future work. This paper results from the inquiry referred, and it’s an approach to the production systems of Beira Baixa Merino. Some constraints to the developpment are pointed.